The Iranian sea-air-missile threat to gulf shipping - Cordesman, Anthony H.; Lin, Aaron (CSIS report, 2015)
"The Arabian Gulf is now involved in a massive arms race, triggered largely by the fear that Iran will try to use its military forces to intimidate or dominate its neighbors. Iran has threatened to close the Gulf and carried out a wide range of large military exercises to show its capabilities. And Iran has steadily increased its ability to exploit the threat of conventional and asymmetric warfare to maritime traffic in the Gulf. The buildup of Iran's naval, air, and missile capabilities poses a wide range of threats to maritime traffic into and outside of the Gulf. One potential target of this threat is the steady increase in bulk cargo shipments into the Gulf, Arabia Sea/Gulf of Oman, and Red Seas -- shipments that are of steadily growing strategic importance to each of the other the Gulf states"--Publisher's web site